P277 State of the Union - An Assessment of Current Adult Asthmatics, Their Demographics, Treatment and Outcomes in 210 Practises Across the UK. (19th November 2012) - Price, D; Ryan, F; Mascarenhas, L; West, D; Gould, S; Hutton, C; Ryan, D
Abstract : Introduction and Objectives: Previous studies have shown that overall asthma care can vary greatly between practises. In this study we evaluate the recorded asthma prevalence and characterize asthma control and risk profiles of real-life asthma patients from 210 practises managed within UK primary care. Methods: Electronic practise data was extracted from patients with asthma from 210 practises across the UK Patients included in the analysis were ≥18 years, had clinician-diagnosed asthma (defined as a diagnostic Read code compatible with the UK Quality and Outcomes Framework [QoF] for asthma) and were receiving current asthma therapy (≥1 asthma prescriptions within the last 2 years). Eligible patients were sent asthma management questionnaires to capture patient-reported outcomes. Pooled practise and patient data were used to characterize patients in terms of their control status (as classified by the Global INitiative for Asthma [GINA] and Royal College of Physician three questions [RCP3]) and risk status (stratified according to exacerbation frequency [Read code defined acute exacerbations and number of courses of acute oral steroids in previous 12 months], with high risk defined as ≥2 exacerbations annually). Results: From 210 practises across the UK there was an asthma prevalence of 5.9%, comprising 80280 adult patients and comparing to a UK QoF-assessed prevalence of 5.8%. The percentage of patients per practise with uncontrolled asthma (Median [IQR]) was 18.8% (9.1, 26.7) while the percentage per practise with no recorded RCP3 data was 18.9 (12.4, 45.9). 3.2% (n=2594) of the patients were classified as being high risk. Conclusions: A high proportion of patients managed in routine UK primary care have sub-optimal asthma control. More patients at BTS management stages 4 and 5 have uncontrolled asthma and suffer from a greater number of exacerbations. RCP3 recording varies between practises, and can be poorly recorded.